Aplicación de Tiras Reactivas Accu-Chek® como microelectrodos económicos para investigación BIA - Lexequias Cabrera, Christian Hugo (2021)
In the midst of an investigation to perform bioelectrical impedance analysis (BIA), we were faced with the need to search for optimally adjusted electrodes to perform reading in small biological samples. The best option to carry out these readings is the well-known gold microelectrodes; however, these are very expensive for our research purposes. For this reason, we found an alternative using Accu-Chek Performa test strips as reading microelectrodes due to their low cost and ease of disposal. This article contains an in-depth detail of the components of the Accu-Chek Performa test strip and the process that was used so that they could be suitable for taking measurements on biological material. In addition, a measurement scheme is shown in conclusion to the operation of the test strip as a microelectrode and the possible problems to consider if it is to be used for future research.